Aligning IT Governance with Organizational Communication Strategies for Enhanced Connectivity - Harjono Padmono Putro (SEAN Institute, 2022)
n today's dynamic business landscape, effective communication and seamless connectivity are critical to organizational success. This research explores the intersection between Information Technology (IT) governance and organizational communication strategy, aiming to uncover synergies that can increase connectivity within an organization. This study explores current IT governance practices and communications strategies, identifying potential misalignments and areas for improvement. Through qualitative descriptive analysis, this research seeks to develop a framework that aligns IT governance with communications strategy, thereby fostering a more cohesive and connected organizational environment. Research shows that aligning the way information technology (IT) is managed with an organization's communication strategy has a positive impact on connections between organizational members. Creating a culture of open communication, aligning organizational messages with IT governance issues, and involving organizational leaders, particularly in IT, have proven crucial in achieving this balance. An approach that takes into account the differences in communication preferences of organizational members, supported by training and the use of modern communication technology, provides a strong basis for understanding and implementing IT governance. As a result, organizations can increase member engagement, create a responsive environment, and support innovation. Thus, this research emphasizes that aligning IT governance with organizational communication strategies is not only a response to technological developments, but also a strategic step for organizational success and sustainability amidst continuous change.